1. А) (a+3)(a-7)-2a(3a+5) = а^2 - 7а + 3а - 21 - 6а^2 - 10а = -5а^2 -14а - 21
Б) 4b(b-2)+(b-4)² = 4b^2 - 8b + b^2 - 8b + 16 = 5b^2 - 16b + 16
В) 3(y+2)²-91 = 3 (y^2 + 4y + 4) - 91 = 3y^2 + 12 y + 12 - 91 = 3y^2 + 12 y - 79
2. a) c³-16c = c (c^2 - 16) = c (c-4)(c+4)
b) 3a²-6a+2a² = 5a^2 - 6a = a (5a-6)
3. (3x-x²)²-x²(x+2(x-2)+2x(7+3x³) = 9x^2 - 6x^3 + x^4 - x^2 (x^2 - 4 + 14x + 6x^4) = 9x^2 - 6x^3 + x^4 - x^4 + 4x^2 - 14x^3 - 6x^6 = 13x^2 - 20x^3 - 6x^6
4. a) 16a⁴ - 1 = (4a^2 - 1) (4a^2 + 1) = (2a - 1) (2a + 1) (4a^2 + 1)
b) a-a²+b+b² = (a + b) - (a^2 - b^2) = (a + b) - (a + b) (a - b) = (a + b) (1 - a + b)
Объяснение:
1).
10a^5 b^3 -18a^3 b^7=2a^3 b^3 •(5а^2 -9b^4)
(х+5)(5а+1)-(х+5)(2а-8)=(х+5)(5а+1-2а+8)=(х+5)(3а+9)=3(х+5)(а+3)
3а-3b+ax-bx=3(a-b)+x(a-b)=(3+x)(a-b)
x^2 -2xy+x-xz+2yz-z=x(x-2y+1)-z(x-2y+1)=(x-z)(x-2y+1)
2).
12х-4х^2=0
4х(3-х)=0
4х=0
х1=0/4=0
3-х=0
х2=0+3=3
(х-9)(4х+3)-(х-9)(3х-1)=(х-9)(4х+3-3х+1)=(х-9)(х+4)
3).
16^5 -8^6=(2×8)^5 -8^6=(2×2^3)^5 -(2^3)^6=(2^4)^5 -(2^3)^6=2^20 -2^18=2^18 ×(2^2 -1)=2^18 ×(4-1)=3×2^18, где одно из производных кратно трем (3:3=1). Следовательно, ответ также будет кратным 3.